Latitudinal variation of the specific local time of postmidnight enhancement peaks in F layer electron density at low latitudes: A case study - Chunhua Jiang (2018)
©2016. American Geophysical Union. All Rights Reserved. Ionospheric nighttime enhancements are manifested in an increase of the electron density at nighttime. This paper studies the latitudinal variation of the specific local time of postmidnight enhancement peaks using ionosondes distributed at low latitudes. To obtain the parameters of the ionosphere, we manually extracted ionograms recorded by ionosondes. Cases show that there are significant latitudinal variations in the observed local time of the postmidnight enhancement peaks. Results show that the lower the geomagnetic latitude, the earlier the enhancement peak occurred in the geomagnetic northern hemisphere. Additionally, the enhancement peaks occurred earlier in the geomagnetic southern hemisphere than that in the geomagnetic northern hemisphere for these present cases. We suggest that the combined effect of the geomagnetic inclination and transequatorial meridional wind might be the main driving force for latitudinal variation of the local time of the occurrence.